2022
DOI: 10.1051/0004-6361/202244593
|View full text |Cite
|
Sign up to set email alerts
|

The GAPS Programme at TNG

Abstract: Aims. We present a novel method for studying the thermal emission of exoplanets as a function of orbital phase at very high spectral resolution, and use it to investigate the climate of the ultra-hot Jupiter KELT-9b. Methods. We combine three nights of HARPS-N and two nights of CARMENES optical spectra, covering orbital phases between quadratures (0.25 < ϕ < 0.75), when the planet shows its day-side hemisphere with different geometries. We co-add the signal of thousands of Fe i lines through cross-correlation,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 96 publications
2
11
1
Order By: Relevance
“…However, as the evidence for Ca II emission is only at the 3.1σ level, this interpretation should be confirmed with additional observations. We robustly detected neutral iron in emission, confirming the previous detections of Fe I emission at high resolution by Pino et al (2020Pino et al ( , 2022 and Kasper et al (2021).…”
Section: Detected Speciessupporting
confidence: 88%
See 3 more Smart Citations
“…However, as the evidence for Ca II emission is only at the 3.1σ level, this interpretation should be confirmed with additional observations. We robustly detected neutral iron in emission, confirming the previous detections of Fe I emission at high resolution by Pino et al (2020Pino et al ( , 2022 and Kasper et al (2021).…”
Section: Detected Speciessupporting
confidence: 88%
“…We robustly detected neutral iron in emission, confirming the previous detections of Fe I emission at highresolution by Pino et al (2020Pino et al ( , 2022 and Kasper et al (2021).…”
Section: Detected Speciessupporting
confidence: 88%
See 2 more Smart Citations
“…Due to the level of precision offered by HRS (and the fact that planets are multidimensional objects), three-dimensional (3D) atmospheric models are ideal for interpreting these spectra. Previous work has found that not only do 3D effects show up in high-resolution transmission (Louden & Wheatley 2015;Flowers et al 2019) and emission (Herman et al 2022;Pino et al 2022;van Sluijs et al 2023) spectra, but detection strengths can increase when using spectra generated from a 3D model compared to 1D models (Beltz et al 2021). Typically the 3D structure of exoplanet atmospheres are simulated with general circulation models (GCMs).…”
Section: Introductionmentioning
confidence: 99%

The Mantis Network

Hoeijmakers,
Kitzmann,
Morris
et al. 2024
A&A